Coelomocyte populations in the sea urchin, Strongylocentrotus purpuratus, undergo dynamic changes in response to immune challenge - Barela Hudgell, Megan A.; Grayfer, Leon; Smith, L. Courtney (Frontiers in Immunology, 2022)
The sea urchin, Strongylocentrotus purpuratus has seven described populations of distinct coelomocytes in the coelomic fluid that are defined by morphology, size, and for some types, by known functions. Of these subtypes, the large phagocytes are thought to be key to the sea urchin cellular innate immune response. The concentration of total coelomocytes in the coelomic fluid increases in response to pathogen challenge. However, there is no quantitative analysis of how the respective coelomocyte populations change over time in response to immune challenge. Accordingly, coelomocytes collected from immunoquiescent, healthy sea urchins were evaluated by flow cytometry for responses to injury and to challenge with either heat-killed Vibrio diazotrophicus, zymosan A, or artificial coelomic fluid, which served as the vehicle control. Responses to the initial injury of coelomic fluid collection or to injection of V. diazotrophicus show significant increases in the concentration of large phagocytes, small phagocytes, and red spherule cells after 1 day. Responses to zymosan A show decreases in the concentration of large phagocytes and increases in the concentration of small phagocytes. In contrast, responses to injections of vehicle result in decreased concentration of large phagocytes. When these changes in coelomocytes are evaluated based on proportions rather than concentration, the respective coelomocyte proportions are generally maintained in response to injection with V. diazotrophicus and vehicle. However, this is not observed in response to zymosan A and this lack of correspondence between proportions and concentrations may be an outcome of clearing these large particles by the large phagocytes. Variations in coelomocyte populations are also noted for individual sea urchins evaluated at different times for their responses to immune challenge compared to the vehicle. Together, these results demonstrate that the cell populations in sea urchin immune undergo dynamic changes in vivo in response to distinct immune stimuli and to injury and that these changes are driven by the responses of the large phagocyte populations.